Medication risk checklist for older adults (LOTTA) - development and validation of a self-assessment tool - Dimitrow Maarit; Saarenmaa Roosa; Airaksinen Marja; Hassan Ghada; Puumalainen Emmi; Pitrová Markéta; Kivelä Sirkka-Liisa; Fialová Daniela; Puustinen Juha; Toivo Terhi (Taylor & Francis, 2025)
Background
Patient safety strategies highlight patients’ own active involvement in ensuring medication safety. A prerequisite for involving patients in their medication therapy is having tools that can assist them in ensuring safe medicine use. Older home-dwelling adults with multiple medications are at high risk for medication-related problems, yet only a few age-specific patient self-administered medication risk screening tools exist. This study aimed to develop, validate, and assess the feasibility of a self-administered medication risk checklist for home-dwelling older adults ≥65 years.
Materials and methods
The draft checklist was formed based on a validated practical nurse-administered Drug Related Problem Risk Assessment Tool supplemented with findings from two systematic literature reviews. The content validity of the draft checklist was determined by a three-round Delphi survey with a panel of 19 experts in geriatric care and pharmacotherapy. An agreement of ≥80% was required. A feasibility assessment (i.e. understandability of the items, fill-out time of the checklist) of the content-validated checklist was conducted among older adults ≥65 years (n = 87) visiting community pharmacies (n = 4). Data were analysed using qualitative content analysis.
Results
The final validated and feasibility-tested Medication Risk Checklist (LOTTA) for home-dwelling older adults consists of eight items screening the highest priority systemic risks (three items), potentially drug-induced symptoms (one item), adherence, and self-management problems (four items). The checklist proved feasible for self-administration, the mean fill-out time being 6.1 min.
Conclusions
A wide range of potential medication risks related to the medication use process can be identified by patient self-assessment. Screening tools such as LOTTA can enhance early detection of potential medication risks and risk communication between older adults and their healthcare providers. A wider and more integrated use of the checklist could be facilitated by making it electronically available as part of the patient information systems.
KEY MESSAGES
Patient safety strategies highlight patients’ own active involvement in ensuring medication safety, which in turn, requires easy-to-use tools to self-assess potential medication risks and communicate them with healthcare providers.
This study produced a short, age-specific eight item Medication Risk Checklist (LOTTA) to be self-administered by home-dwelling older adults to identify major systemic risks, potential drug-induced symptoms, adherence, and self-management problems related to medication taking.
To facilitate the use of the checklist in early detection of potential medication risks, future studies should focus on converting the LOTTA list into electronic form and pilot its use as an integrated part of the electronic patient information system.